1997
DOI: 10.1111/j.1540-8159.1997.tb06077.x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Atrial Pacing in Cardiac Transplant Patients

Abstract: Thirteen out of 223 consecutive cardiac transplant patients required permanent pacemaker implantation; 11 for sinus node dysfunction and 2 for complete AV block. Patients with sinus node dysfunction were considered for AAIR mode pacemakers if they had intact AV conduction defined as a Wenckebach point of > 120 beats/min. Ten of 11 patients with sinus node dysfunction had a single atrial lead placed. Atrial lead placement was most easily accomplished with a straight, active fixation lead and the use of manually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
4
4
0
Order By: Relevance
“…Rothman et al noted a similar incidence of SND (42%) in the early postoperative period (defined by nonsinus rhythm on monitoring or the presence of an abnormal sinus node recovery time or secondary pauses when patients were tested in the electrophysiology laboratory) 14 . Early permanent pacemaker implantation rates vary from 2.8% to 29% in different series 1,6, 9,10,15–22 . Our incidence of SND resulting in permanent pacing within the first 30 days is 6.8%, a finding similar to these previously reported results.…”
Section: Discussionsupporting
confidence: 90%
“…Rothman et al noted a similar incidence of SND (42%) in the early postoperative period (defined by nonsinus rhythm on monitoring or the presence of an abnormal sinus node recovery time or secondary pauses when patients were tested in the electrophysiology laboratory) 14 . Early permanent pacemaker implantation rates vary from 2.8% to 29% in different series 1,6, 9,10,15–22 . Our incidence of SND resulting in permanent pacing within the first 30 days is 6.8%, a finding similar to these previously reported results.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, we are cautious about drawing conclusions about survival in patients with late‐onset AV block due to the small number of patients in this study. Nonetheless, our data are consistent with previous reports, suggesting no effect on long‐term survival in patients with late‐onset AV block requiring permanent pacemaker 6,8,9,17,18 …”
Section: Study Limitationsupporting
confidence: 93%
“…Some studies suggested late‐onset SND and others AV block as the dominant indication for permanent pacing, although the number of patients were generally small (Table III). 4 , 7–11 , 13–16 This study, with 27 patients who required permanent pacing >3 months from heart transplant (13 [48.2%] due to SND and 14 [51.8%] due to AV block) add to these previous reports and suggest that both SND and AV block may contribute equally to the need for permanent pacing late after heart transplantation.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations